Bibliometric analysis of Dermochelys coriacea in Mexico using Vosviewer and Scopus (Nexo Revista Científica, 2022)
In the present study, a bibliometric analysis was carried out on the species Dermochelys coriacea in the Scopus database for the last ten years. Two inquiry analyzes were used (co-authorship and co-presence), from the VOSviewer version 1.6.17 software. The items Dermochelys coriacea, and Mexico were used to search for relevant publications. A total of 7 articles were found during the period 2010 - 2021, in each year there was at least one publication. The author who published the most on this species is García-Grajales (N=2) (Universidad del Mar) and the state that recorded the most articles on the species is Oaxaca (N=4). The topics of Ecology and Microbiology have been the most addressed and a total of 52 authors with articles on D. coriacea in Mexico were registered. The keywords provided by the authors of the articles were a total of 66, three of which reached the threshold. The words that appeared most frequently were: Dermochelys coriacea, leatherback and morphology.